CONSIDERAÇÕES SOBRE OS ASPECTOS E IMPACTOS AMBIENTAIS PARA O FECHAMENTO DO SISTEMA DE REFRIGERAÇÃO DE UMA REFINARIA DE PETRÓLEO LOCALIZADA NA ORLA DA BAÍA DE GUANABARA, RJ - Camaz, Fernando Ribeiro (2008)
The use of trustworthy environmental performance indicators and the dissemination of eco-efficiency indicators are measured necessary to give transparency to the businesses of companies. The analysis of these indicators can guide environmental investments necessary to keep a sustainable level of natural capital. In this work we will have as objective to scientifically evaluate the environmental aspects and impacts of the closure of the Duque de Caxias Refinery (REDUC) open refrigeration system, mentioned in the Term of Commitment for Adjustment of the Environment signed between Petrobras and the Rio de Janeiro State Government in November 2000. It was also analyzed the descriptive statistical treatment of the behavior of the of oils and greases launched in Guanabara Bay, as shown in the reports of the PROCONÁGUA, sent to the State Environmental Agency (FEEMA), in the period of the research from January 1998 to October 2006. The complexity of the Term of Commitment for Adjustment of the Environment of REDUC inserts an additional difficulty of analysis, when it is intended to quantify the final environmental results of the Term implementation. In the case study, it is described the company, its environmental pollution and historical potential and its planning and management tools. Although the results are significant, there is a difficulty in making a direct correlation with the effect of the produced cultural change, being complex to measure environmental profits, direct and indirect, in the this northwest region of the Guanabara Bay. The proposal presented in the conclusions could be a practical instrument for the environmental management of an oil refinery and other companies for consolidating the history and the performance indicators, as instrument of information for the decision making of process of organizations. Then, it will be possible to evaluate the environmental performance of an organization in a time period.